The Relationship Between Socioeconomic Characteristics and Competence of Rice Seed Producers - Hadi Kosra; Linar Humaira; Roznaliza Testiana (Indonesian Journal of Social Research (IJSR), 2021)
Bogor Regency is one of the areas that has a large enough rice seed business potential that can support the Seed Independent Village program. However, the availability of seeds needs to be supported by the resources and competence of the farmers around them, so they do not depend on other areas as seed producers. The purpose of this study was to analyze the relationship between farmer characteristics socioeconomics and the competency level of rice seed producers in Bogor Regency, West Java. This study used a survey method of 59 rice seed producers who were scattered in three sub-districts of Bogor Regency which were determined by stratified random sampling. The variables observed were farmer socioeconomics characteristics, management competence aspects and technical aspects of production. The data analysis used descriptive statistical analysis and the rank spearman inferencing statistics. The results showed that the competence level of rice seed producers from the management aspect was categorized quite high, while the competency level from the technical aspect was 71.4% in the low category. The factors that have a relationship with the competence of rice seed producers are length of business, land area, motivation, production, income, counseling and access to capital